Powstanie i rozwój kolei żelaznych w prowincji Pomorze jako wyraz aktywności lokalnych środowisk i sektora publicznego - Myszczyszyn, Janusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2017)
The creation and development of railways in Prussia in the first two decades of their existence occurred by the private sector. Prussian state established railway law on 3 November 1838, the Berlin–Szczecin railway built relatively early line Berlin–Szczecin (1843) and Stargard–Szczecin (1846). Development of the railway was an important event for the province and Szczecin, affecting the economic, social and political importance. Prussian government has been actively involved in the process of construction of the railway in the early eighties of the 19th century. Local government have been active since 1892, which was related to the new law on local railways construction (Gesetz über Kleinbahnen und Privatanschlußbahnen vom 28.07.1892). Local authorities (eg. provincial assembly, counties, local municipalities) became an active participant in economic life, including the development of narrow-gauge railway infrastructure in Pomerania.